(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
education is the basis upon which scientific and professional competencies are built to measure and communicate economic events and provide appropriate information for decision-making. Therefore, the IFACB has issued international standards that include most of the important aspects of building the capacity of accountants and providing them with the required knowledge and skills, which ultimately results in providing the accounting profession with qualified and trained scientific and practical staff to lead the market efficiently and effectively. , So as to ensure the pace of economic and social development plans that the States and their governments seek to achieve The aim of this research is to clarify the role of international accounting education standards and propose a comprehensive framework based on these standards of international accounting education in line with the accounting education environment in Iraq and meet the required academic and professional accounting requirements The research has reached a number of conclusions, the most important of which is the possibility of benefiting from the standards of international accounting education in developing the learning outcomes and professional skills of the educational institutions in order to achieve the efficiency and effectiveness of the aspects of preparing and rehabilitating the scientific and practical. In addition, the development of the educational process has been imposed by the changes and developments of the international business environment in general and local Especially The study presented a set of recommendations, the most important of which is the need to apply the standards of international accounting education by institutions that deal with accounting education from universities and institutes of Iraq to improve the level of students in terms of scientific and practical and achieve compatibility between accounting education and practical reality